Analysis of the Biological and Chemical Reactivity of Zeolite-Based Aluminosilicate Fibers and Particulates - Fach, Estelle; Waldman, W. James; Williams, Marshall; Long, John; Meister, Richard K.; Dutta, Prabir K. (Environmental health perspectives, 2002)
Environmental and/or occupational exposure to minerals, metals, and fibers can cause lung diseases that may develop years after exposure to the agents. The presence of toxic fibers such as asbestos in the environment plus the continuing development of new mineral or vitreous fibers requires a better understanding of the specific physical and chemical features of fibers/particles responsible for bioactivity. Toward that goal, we have tested aluminosilicate zeolites to establish biological and chemical structure-function correlations. Zeolites have known crystal structure, are subject to experimental manipulation, and can be synthesized and controlled to produce particles of selected size and shape. Naturally occurring zeolites include forms whose biological activity is reported to range from highly pathogenic (erionite) to essentially benign (mordenite). Thus, we used naturally occurring erionite and mordenite as well as an extensively studied synthetic zeolite based on faujasite (zeolite Y). Bioactivity was evaluated using lung macrophages of rat origin (cell line NR8383). Our objective was to quantitatively determine the biological response upon interaction of the test particulates/fibers with lung macrophages and to evaluate the efficacy of surface iron on the zeolites to promote the Fenton reaction. The biological assessment included measurement of the reactive oxygen species by flow cytometry and chemiluminescence techniques upon phagocytosis of the minerals. The chemical assessment included measuring the hydroxyl radicals generated from hydrogen peroxide by iron bound to the zeolite particles and fibers (Fenton reaction). Chromatography as well as absorption spectroscopy were used to quantitate the hydroxyl radicals. We found that upon exposure to the same mass of a specific type of particulate, the oxidative burst increased with decreasing particle size, but remained relatively independent of zeolite composition. On the other hand, the Fenton reaction depended on the type of zeolite, suggesting that the surface structure of the zeolite plays an important role.